CALCULATION METHOD IMPROVEMENT FOR CONTACT FATIGUE RELIABILITY OF CYLINDRICAL HELICAL GEAR - MA Dong; CUN LiGang; LIU YanHu; LIN YiZhe (Jixie qiangdu)
Reliability and fuzzy theory was applied to analyze the contact fatigue reliability of cylindrical helical gear. Furthermore, the calculation method has been improved. The reliability for contact fatigue of cylindrical helical gear after working a period of time was obtained used Matlab as a tool for numerical simulation and it has been compared with the results based on general approaches. The result shows that the improved method is more comprehensive consideration than general methods. Moreover, it provides a reference for reliability calculation of the gear.